The people vs. democracy why our freedom is in danger and how to save it - Mounk, Yascha, 1982- (Harvard University Press, 2018)
From India to Turkey, from Poland to the United States, authoritarian populists have seized power. Two core components of liberal democracy--individual rights and the popular will--are at war, putting democracy itself at risk. In plain language, Yascha Mounk describes how we got here, where we need to go, and why there is little time left to waste.--